Media Kajian Pancasila dan Kewarganegaraan: Analisis Kemunculan Gerakan Pendukung Kotak Kosong Pada Pemilihan Kepala Daerah Di Kabupaten Pasaman Tahun 2022 - ahmad sabil (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2025)
Title in English. This journal discusses the factors that led to the emergence of the empty column movement in the implementation of the Pasaman Regency Pilkada in 2020. The purpose of this research is to describe the reasons behind the emergence of the empty column movement. The approach used in this research is qualitative with a case study method. This research is analyzed using the concept of mobilization according to Stefano B. The results showed that there were main factors and supporting factors that led to the emergence of the empty column movement in the 2020 Pasaman Regency Pilkada. The main factor that triggered the birth of the empty column movement was the dynamics of the Pilkada which was considered unique and interesting, which then resulted in a single candidate in the Pilkada. This situation has led to a deep sense of disappointment in some Pasaman people who want change, especially related to the leadership in Pasaman Regency, which has been dominated by the incumbent. Through the empty column movement, the people of Pasaman explicitly expressed their desire to have a new, more competent leader.